2009
DOI: 10.1002/art.24361
|View full text |Cite
|
Sign up to set email alerts
|

Ro 60 functions as a receptor for β2‐glycoprotein I on apoptotic cells

Abstract: Objective. The autoantigens 60-kd Ro/SSA (Ro 60) and ␤ 2 -glycoprotein I (␤ 2 GPI) are both displayed on the surface membrane of apoptotic cells. Epitopespreading experiments have suggested that these autoantigens may be present as a complex on the apoptotic cell surface. This study was undertaken to investigate whether ␤ 2 GPI interacts with Ro 60 on apoptotic cells and alters the binding of anti-Ro 60 IgG.Methods. The interaction between soluble recombinant Ro 60 fragments and ␤ 2 GPI was investigated in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Because it does not span the membrane, the way it works remains to be established (55). Finally, data has just been published (22) that b2-gpI binds to the 60-kDa Ro protein on apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it does not span the membrane, the way it works remains to be established (55). Finally, data has just been published (22) that b2-gpI binds to the 60-kDa Ro protein on apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…This electrostatic symmetry needs to be reinforced by a sound link between 2 aa sequences, one in the cofactor and another in unknown receptors on the membrane. Candidates include megalin (19), annexin A2 (20), aplipoprotein E receptor 2 (21), and Ro60 exposed on apoptotic blebs (22). The binding of stable b2-gpI-containing immune complexes to any of these receptors (23) is assumed to trigger a cascade of kinases (24) conveyed through dynamic assemblies of cholesterol and cholera toxin B (CTB)-binding ganglioside M1 termed lipid rafts (LRs).…”
mentioning
confidence: 99%
“…2): UCHL5 (MIM: *610667) encodes a deubiquitinating enzyme known to associate with 26 proteasomes (Hamazaki et al, 2006), and found unregulated in uterine cervical neoplasms (Rolen et al, 2006); TROVE2 (MIM: *600063) encodes a protein that functions as a receptor for beta(2)-glycoprotein I on apoptotic cells (Reed et al, 2009); GLRX2 (MIM: *606820) has been recognized to encode an important redox regulator in mammalian organs including heart (Nagy et al, 2008); and B3GALT2 (MIM: *603018), an overlapping RNA transcribed in opposite direction to CDC73, encodes a protein that functions in Nlinked glycoprotein glycosylation. No other clinical signs apart from those fitting the HPT-JT syndrome were found in this family, suggesting that all these genes are haplosufficient.…”
Section: First Gross Cdc73 Germline Deletionmentioning
confidence: 99%
“…The function of ␤2GPI remains uncertain, although it is thought to play a role in apoptotic cell clearance and coagulation through multiple interactions with serine proteases, anionic phospholipid, and cell-surface receptors. [13][14][15][16][17][18][19][20] It is found in relatively high concentrations in circulating plasma (4M) and is also found within atherosclerotic plaque lesions, 21 although the function of ␤2GPI relating to atherosclerosis has not been elucidated. The antiphospholipid syndrome is an autoimmune condition characterized by pathogenic circulating anti-␤2GPI antibodies.…”
Section: Introductionmentioning
confidence: 99%